Externality of Economic Diplomacy in Indonesia: Case Study of Investment within Palm Plantation Sector - Pattinussa, Jhon Maxwell Yosua; Tambunan, Edwin M.B. (Global Strategis, 2023)
The rapid global trade has made the role of economic diplomacy becoming more significant for Indonesia. However, as international cooperation strengthened and investment flows increased following the success of economic diplomacy, externality towards the environment also appeared. By using green political theory as a theoretical basis, this article reveals how Indonesia's economic diplomacy has overlooked environmental considerations and harmed the nature. This article uses an analytical framework highlighting commercial policy, assets as bargains, and laws governing business to examine the oil palm plantation case in Boven Digoel, Papua. Based on secondary data obtained from relevant literature and primary data collected through interviews, this research finds that the reliance of Indonesia's economic diplomacy on commercial paper UU PMA 1967 (the 1967 Foreign Investment Law), forest assets offered as bargaining chips, and laws governing business as stated in PP.33/Menhut/2010 has resulted on the state's neglect of nature protection. Keywords: Economic Diplomacy, Externalities, Green Political Theory, Natural Resources, Commercial Policy.   Meningkatnya perdagangan global menyebabkan diplomasi ekonomi semakin penting bagi Indonesia. Namun, arus investasi dan menguatnya kerja sama internasional sebagai hasil dari diplomasi ekonomi ternyata menimbulkan eskternalitas terhadap lingkungan. Dengan menggunakan teori politik hijau sebagai landasan teori, tulisan ini mengungkap bahwa diplomasi ekonomi yang tidak mempertimbangkan aspek lingkungan menyebabkan kerusakan alam. Artikel ini menggunakan kerangka analisis yang menyoroti commercial policy, assets as bargain, dan hukum yang mengatur bisnis untuk menelaah kasus perkebunan kelapa sawit di Boven Digoel, Papua. Analisis dikembangkan secara kualitatif berdasarkan data sekunder yang didapat dari berbagai sumber kepustakaan yang relevan dan data primer yang dikumpulkan melalui wawancara penelitian ini menemukan bahwa dalam praktiknya diplomasi ekonomi mengabaikan kepentingan lingkungan. UU PMA 1967, aset yang ditawarkan, dan PP.33/Menhut/2010 merupakan bentuk dari pengabaian pemerintah terhadap perlindungan alam. Kata-kata Kunci: Diplomasi Ekonomi, Eksternalitas, Teori Politik Hijau, Sumber Daya Alam, Kebijakan Komersial.